Development of Hardware Interfacing System for Visual C++ - Doyce T Martinez; Tomas Ucol Ganiron Jr; Catherine S Lacsamana (Institute of Advanced Engineering and Science, 2013)
This paper discussed on the development of automated data acquisitioncircuits using the parallel port of a computer through Visual C++. The aim ofthis study is to produce low cost laboratory apparatus that are both accurateand easy to use. Two revisions of an accelerometer device are described in thispaper. Each prototype determined sources of errors (initial moment of inertia,device delay, code optimization) that were used in improving the design for thenext revision. For the first revision errors of 13.63% and 16.38% between theexperimental and theoretical values were recorded while the second revisionshowed errors of 12.58 % and 7.20 % on two different angles. The next revisionof the prototype would include the use of embedded assembly code in the Visual C++code together with advanced thread synchronization techniques to improve theaccuracy of the measured data.